The Effect Of The Concept Sentence Model Assisted By Flashcard Media On The Writing Skills Of Descriptive Essays Of Fifth Grade Students At UPTD SD Negeri 353 Bulete, Wajo Regency - Elzha Amalia Amanda; Rahmawati Patta; Syamsuryani Eka Putri Atjo (International Journal of Elementary School Teacher, 2026)
This research is based on the problem of low writing skills in descriptive essays among students. The objectives of this research are: (1) to understand the implementation of the Concept Sentence learning model assisted by flashcard media on students' descriptive writing skills; (2) to assess students' descriptive writing skills; and (3) to determine the effect of applying the Concept Sentence model assisted by flashcard media on the descriptive writing skills of fifth-grade students at UPTD SD Negeri 353 Bulete, Wajo Regency.This research employs a quasi-experimental design of a non-equivalent group type. The population and sample for this study consist of all fifth-grade students at UPTD SD Negeri 353 Bulete, Wajo Regency, totaling 30 students selected through saturated sampling techniques. Data were collected using documentation, observation sheets, and tests administered before and after the learning process. Data analysis techniques included descriptive statistical analysis and inferential statistical analysis.The results of the descriptive analysis indicate that the implementation of the Concept Sentence learning model assisted by flashcard media was effective in the first meeting and very effective in the second meeting. Inferential analysis using an independent sample t-test revealed a significant difference in post-test results between the experimental class and the control class. This indicates an improvement in students' critical thinking abilities in mathematics within the experimental group.Thus, it can be concluded that: (1) the learning process using the Concept Sentence model assisted by flashcard media was very effective; (2) student test results showed an increase in descriptive writing skills; and (3) there is a significant effect of applying the Concept Sentence model assisted by flashcard media on the descriptive writing skills of fifth-grade students at UPTD SD Negeri 353 Bulete, Wajo Regency